Efeitos cardiorrespiratórios da associação de tiletamina/zolazepam em cães (Canis familiaris) pré-tratados ou não pela acepromazina - ALMEIDA, Ellen Maria Pestili de [UNESP]; NUNES, Newton [UNESP]; FANTINATTI, Alexandra Pinheiro [UNESP]; Santos, Paulo Sergio Patto dos [UNESP]; BOLZAN, Aline Adriana [UNESP]; REZENDE, Márlis Langenegger de [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 2000)
Avaliou-se o uso da acepromazina como pré-tratamento à associação de tiletamina/zolazepam. Para tanto, utilizaram-se 20 animais da espécie canina, machos e fêmeas, adultos, hígidos, divididos em 2 grupos de igual número. O grupo 1 (controle) foi pré-tratado com 0,1 ml/kg de solução salina a 0,9 % e o grupo 2 com 0,2 mg/kg de acepromazina, ambos por via intravenosa. Decorridos 20 minutos, todos os animais receberam, pela mesma via, 10 mg/kg da associação tiletamina/zolazepam. Imediatamente antes da medicação pré-anestésica (M1), antes da aplicação da associação (M2) e aos 15, 30, 45 e 60 minutos após a administração da tiletamina/zolazepam, realizou-se mensuração de: freqüência cardíaca (FC); pressão arterial sistólica (PAS), diastólica (PAD) e média (PAM); débito (DC) e índice cardíaco (IC); volume sistólico (VS); eletrocardiograma (ECG); freqüência respiratória (FR); CO2 ao final da expiração (ETCO2); saturação da oxiemoglobina (SpO2); e temperatura retal (T0). Observou-se estabilidade cardiovascular, miorrelaxamento e aumento do período hábil anestésico com o uso da acepromazina na medicação pré-anestésica. O tratamento estatístco dos valores numéricos pela análise de perfil mostrou que a acepromazina diminuiu a FR; entretanto, a SpO2 e ETCO2 não sofreram alterações estatisticamente significativas, permitindo concluir que o emprego da fenotiazina apresenta vantagens sobre o uso isolado da associação tiletamina/zolazepam, em cães.

The aim of this work was to evaluate the use of acepromazine as pre-treatment to tiletamine/zolazepam association. Twenty male and female healthy adult mixed breed dogs were used. The dogs were allocated in two groups of 10 animals each (G1 and G2). To G1 was administered 0.1 ml/kg of saline at 0.9 % (placebo), followed by 10 mg/kg of tiletamine/zolazepam 20 minutes later, both intravenously. Immediately before the pre-anesthetic medication (M1), before the anesthetic s application (M2) and at 15, 30, 45 and 60 minutes after the administration of tiletamine/zolazepam association (M3 to M6, respectively), measurements of heart rate (HR), systolic, diastolic and mean blood pressures (SBP, DBP e MBP, respectively), cardiac output (CO), cardiac index (CI), systolic volume (SV), electrocardiogram (ECG), respiratory rate (RR), end tidal CO2 (ETCO2), oxihemoglobin saturation (SpO2) and body temperature (T0) were realized. For G2 the same methodology was used, replacing the placebo by acepromazine, at 0.2 mg/kg. The numeric data were submitted to analysis of profile that demonstrated cardiovascular stability and an increase of the anesthetic period with the use of acepromazine, and it was also observed, in G2, that, in spite of the decrease of RR, the SpO2 and ETCO2 values didn t have significant alterations, allowing to conclude that the use of acepromazine presents advantages in the isolated use of the tiletamine/zolazepam association, in dogs.
Cardiorespiratory effects of tiletamine/zolazepam in dogs (Canis familiaris) given acepromazin
Keywords: Cão; Acepromazina; Tiletamina; Zolazepam; Anestesia; Dog; Acepromazine; Tiletamine; Zolazepam; Anaesthesia